Two new species of the genus Anemadus Reitter, 1885, from the Near East (Coleoptera: Cholevidae) - Giachino, Pier Mauro; Latella, Leonardo; Vailati, Dante (Zootaxa, 2013)
Two new species of Anemadus from the Near East are described and illustrated. Anemadus lucarellii sp. nov., from South-Western Anatolia, belongs to the Anemadus pellitus species-group (sensu Giachino & Vailati, 1993) and Anemadus kadleci sp. nov., from North-Western Syria, belongs to the Anemadus strigosus species-group (sensu Giachino & Vailati, 1993). The description of these new species markedly increases the knowledge of the distribution of this genus in the Near East.